Financing Asset Sales and Business Cycles - Arnold, Marc; Hackbarth, Dirk; Xenia Puhan, Tatjana (Review of Finance, 2018)
Abstract Using a dynamic model of financing, investment, and macroeconomic risk, we investigate when firms sell assets to fund investments (financing asset sales) across the business cycle. Equity financed investment transfers wealth from equity to debt because asset volatility declines and earnings increase when firms invest. Financing asset sales reduce asset collateral and, hence, transfer wealth back from debt to equity. Exploring the dynamics of the heretofore overlooked “asset sale versus external equity” financing margin across business cycles helps explain novel stylized facts about asset sales and their business cycle patterns that cannot be rationalized by traditional motives for selling assets.